'This foul slavery-reviving system': Irish opposition to the Jamaica Emigration Scheme. (2nd July 2016) - Murphy, Angela F.
ABSTRACT: Following the end of slavery and apprenticeship in British Jamaica, the Jamaican House of Assembly instituted an immigration program to bring indentured workers to the island in order to counteract the ability of the emancipated black slaves to demand high wages. In 1840 Ireland became a target for the recruitment of such indentures, but almost immediately Irish humanitarians protested the 'Jamaica Emigration Scheme', calling it slavery under another name. Efforts to attract Irish laborers in Limerick to board the Robert Kerr, an emigrant ship bound for Jamaica, sparked their activity, and their agitation continued in the aftermath of its departure in January 1841. Irish abolitionists affiliated with the Hibernian Anti-Slavery Society and Irish nationalists affiliated with Daniel O'Connell's Loyal National Repeal Association organized against the attempt to indenture Irish workers in Jamaica. This article explores the reasons why and the ways in which members of both organizations cooperated in their protests against the Jamaica Emigration Scheme. In particular, it examines what their interactions reveal about the motives of each organization, the relationship between antislavery activism and anti-emigration attitudes, and the ways in which the recruitment of Irish indentures complicated debates among reformers about the nature of free and unfree labor.